The sustainability of collapse for tunnel advance excavation in the rock around the mine Tenggarong Subdistrict, Kutai Kartanegara District, east Kalimantan - Sujiman, Sujiman; Hariyadi, Sundek; Sundoyo, Sundoyo; Sujiman, Muhammad Granit (Edelweiss Applied Science and Technology, 2025)
This study aims to assess the lithological conditions and geological structures of the research area, evaluate collapse characteristics in mining excavations using the advanced tunneling method, and examine the sustainability of mining management to prevent rock collapse. Groundwater data were obtained through falling-head tests, while lithological and structural data were collected from geological mapping. Ecological, economic, social, legal–institutional, and technological data were derived from field observations and expert questionnaires. Based on Rock Mass Rating (RMR) classification, the direct roof has a score of 53.00 and the main roof 58.50. Without support, the average stand-up time for the L layer with a 4 m tunnel advance is approximately 6 days and 16 hours before collapse. The current sustainability status across five dimensions, ecological, economic, social, legal–institutional, and technological, achieved a score of 48.74%, categorized as sufficient. By improving sensitive attributes, this score could increase to 81.74%, representing good sustainability. Accordingly, this study recommends the application of appropriate tunnel support systems, particularly self-advancing supports, and targeted improvements across all sustainability dimensions to ensure safe, stable, and sustainable mining operations.